2003
DOI: 10.1128/mcb.23.15.5143-5164.2003
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Enhancer Factor 1 Binds Multiple Muscle MEF2 and A/T-Rich Elements during Fast-to-Slow Skeletal Muscle Fiber Type Transitions

Abstract: In adult mouse skeletal muscle, ␤-myosin heavy chain (␤MyHC) gene expression is primarily restricted to slow type I fibers; however, its expression can be induced in fast type II fibers in response to a sustained increase in load-bearing work (mechanical overload [MOV]). Our previous ␤MyHC transgenic and protein-DNA interaction studies have identified an A/T-rich element (␤A/T-rich ؊269/؊258) that is required for slow muscle expression and which potentiates MOV responsiveness of a 293-bp ␤MyHC promoter (␤293wt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 63 publications
3
57
0
Order By: Relevance
“…By binding M-CAT sites, TEAD4 participates in muscle-fiber-type switching and mediates in part the transcriptional effects of hypoxia and ␣-adrenergicstimulated muscular hypertrophy (Karasseva et al 2003;Shie et al 2004). Together with the observation that the M-CAT sequence is enriched among MRF targets, this suggests that, besides regulating additional genes during the muscle hypertrophic response (Ueyama et al 2000), TEAD4 propagates the myogenic signal originating from MyoD and cooperates with MRFs to induce the expression of their targets.…”
Section: A Cohort Of Transcription Factors Amplifies Signals Initiatementioning
confidence: 84%
See 1 more Smart Citation
“…By binding M-CAT sites, TEAD4 participates in muscle-fiber-type switching and mediates in part the transcriptional effects of hypoxia and ␣-adrenergicstimulated muscular hypertrophy (Karasseva et al 2003;Shie et al 2004). Together with the observation that the M-CAT sequence is enriched among MRF targets, this suggests that, besides regulating additional genes during the muscle hypertrophic response (Ueyama et al 2000), TEAD4 propagates the myogenic signal originating from MyoD and cooperates with MRFs to induce the expression of their targets.…”
Section: A Cohort Of Transcription Factors Amplifies Signals Initiatementioning
confidence: 84%
“…TEAD4 is closely related to TEAD1 (TEF-1), the founding member of a family of transcriptional regulators that bind M-CAT DNA elements (GGAATG) (Karasseva et al 2003). By binding M-CAT sites, TEAD4 participates in muscle-fiber-type switching and mediates in part the transcriptional effects of hypoxia and ␣-adrenergicstimulated muscular hypertrophy (Karasseva et al 2003;Shie et al 2004).…”
Section: A Cohort Of Transcription Factors Amplifies Signals Initiatementioning
confidence: 99%
“…TEF-1 binds to MCAT sequences [related to CATTCC(A/T)] or A/T-rich sites within the promoter region of many genes, including βMHC (β-myosin heavy chain), cardiac troponin T and skeletal α-actin [1,2]. The above results show that TAZ and YAP65 interact with TEF-1, but the significance of this interaction to transcriptional regulation depends on these interactions occurring while TEF-1 is bound to DNA.…”
Section: Tef-1 and Taz Interact While Bound To Mcat Dnamentioning
confidence: 95%
“…TEF-1 binds to MCAT (muscle C, A and T sites), sequence related to CATTCC(A/T), in promoters active in cardiac, skeletal and smooth muscle, placenta, and neural crest. Recently, R. Tsika and co-workers found that TEF-1 binds weakly to A/Trich binding sites in muscle promoters [2], expanding the promoters that are potentially regulated by TEF-1. The vast majority of cellular promoters that are MCAT-dependent are muscle-specific [1,[3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have also suggested that Tead1 binds to and activates A/T-rich and MEF2 elements on some muscle genes (50). The M-CAT motif was initially identified in the cardiac troponin T promoter, and the interaction of M-CAT motif and an M-CAT binding factor is required for the activation of cardiac troponin T promoter in muscle cells (51).…”
Section: Discussionmentioning
confidence: 99%